Pengaruh Penambahan Serat Kawat Bendrat Terhadap Kuat Lentur Beton Geopolimer - Indrayani Indrayani; Ika Sulianti; Lina Flaviana Tilik; Djaka Suhirkam; Suhadi Suhadi; Muhammad Prawira Wardana; Iros Milawati (Universitas Islam 45, 2022)
Currently, innovation continues to be developed to replace cement with other materials so that the use of cement as a building material can be reduced. Utilization of coal waste (fly ash) is an alternative to subtitude cement. From previous studies, fly ash mixed with alkaline materials in the form of NaOH and Na2SiO3 in a ratio of 1:5 can produce geopolymer concrete. This geopolymer concrete research was continued by adding bendrat wire fibers into the geopolymer concrete mixture. The method used in testing the aggregate, testing the compressive strength of normal concrete K225, testing the flexural strength of normal concrete and geopolymer concrete refers to SNI. Another additional material that is mixed is bendrat wire fiber. The research was carried out in the form of making flexible beams of 10 cm x 10 cm x 50 cm with fiber variations of 0%, 0.5%, and 1,0% at the age of 14 and 28 days. The results of the flexural strength test of the BN beam at the age of 28 days can withstand loads than BG. The average flexural strength obtained with variations of BN, BN+SB 0.5% and BN+SB 1.0% respectively were 2.796 MPa, 3.113 MPa, and 3.879 MPa. The results of testing the average flexural strength of geopolymer concrete beams at 28 days, obtained variations of BG, BG+SB 0.5%, and BG+SB 1.0% respectively were 0 MPa, 0.055 MPa and 0.104 MPa. In addition, geopolymer concrete cannot be used as a beam and the addition of bendrat wire fiber to geopolymer concrete cannot withstand the tensile load on the concrete.